2022
DOI: 10.1371/journal.pgph.0000276
|View full text |Cite
|
Sign up to set email alerts
|

Associations between occupation, leprosy disability and other sociodemographic factors in an endemic area of Brazil

Abstract: Background In Brazil, new leprosy cases with grade-2 disability (G2D) have been increasing. Physical disability has been associated with experienced stigmatization, psychological distress, and social restriction. Objectives To identify factors associated with leprosy disability in an endemic area of Brazil focusing on occupational and other sociodemographic factors. Methods Between July and December 2015, adult patients with multibacillary leprosy who attended a clinic in Belo Horizonte, Brazil were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In G2D patients, a higher level of education was linked to a decreased risk of detection delay; this association was not statistically significant. However, another study found a correlation between lower levels of schooling and a higher prevalence of disabilities in Grades 1 or 2 [ 35 ]. The primary requirements in lowering disabilities among leprosy patients are health education regarding leprosy, knowledge about the provision of accessible and no-cost healthcare facilities, and follow-up of long-duration courses of multidrug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In G2D patients, a higher level of education was linked to a decreased risk of detection delay; this association was not statistically significant. However, another study found a correlation between lower levels of schooling and a higher prevalence of disabilities in Grades 1 or 2 [ 35 ]. The primary requirements in lowering disabilities among leprosy patients are health education regarding leprosy, knowledge about the provision of accessible and no-cost healthcare facilities, and follow-up of long-duration courses of multidrug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 17 studies found that leprosy was associated with male gender, performing manual labour, ever food-shortage, sharing household with another leprosy patient, and communal living with a minimum of 5 occupants [36]. Moreover, risk factors for leprosy-related disabilities include advanced age, male, low education, multibacillary leprosy type, the presence of leprosy reactions, nerve damage, delayed diagnosis, and treatment dropout [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…This includes ensuring the presence of ceilings, utilizing easily cleanable flooring materials, maintaining comfortable humidity levels, and limiting the occupancy of bedrooms to a maximum of two individuals [80]. Conversely, marital status and proximity to healthcare facilities do not significantly affect the likelihood of leprosy-related disability [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that this disease cannot be eliminated by PCT treatment alone 25,26 . There is evidence to suggest that local population, density and level of endemicity play a role in the emergence of leprosy 26,27 . Another factor that should receive more attention is the microenvironment, such as the number of people per household and per room of the house, poor sanitary conditions, genetic susceptibility, low education levels, local social and cultural dynamics and so on 28,29 .…”
Section: Introductionmentioning
confidence: 99%